MiR-571 affects the development and progression of liver fibrosis by regulating the Notch3 pathway - Shuo Cong; Yongmei Liu; Yi Li; Yu Chen; Rui Chen; Baofang Zhang; Lei Yu; Yaxin Hu; Xueke Zhao; Mao Mu; Mingliang Cheng; Zhi Huang (Scientific Reports)
Abstract Exploring the expression of miR-571 in patients with liver fibrosis and its role in the progression of liver fibrosis. A total of 74 patients with liver fibrosis in our institution from September to December 2018 were collected for study, and the expression of miR-571, Notch3 and Jagged1 in patients with different progressions of liver fibrosis was determined by RT-PCR and Western blot analysis. Set up Notch3 up group and Notch3 down regulated group, RT-PCR and Western blot were used to determine the effect of Notch signaling on the expression of fibrogenic factors. CCK-8, cell scratch assays, Transwell assays, flow cytometry were used to determine the effect of miR-571 on LX-2 proliferation, migration, apoptosis in human stem stellate cells, and RT-PCR, Western blot assays were performed to determine the effect of miR-571 on the Notch3 signaling pathway and the expression of profibrogenic factors. miR-571, Notch3 and Jagged1 are up-regulated in patients with liver fibrosis and is associated with the progression of liver fibrosis. Notch3 signaling pathway can promote the expression of fibroblast in human hepatic stellate cells; miR-571 can inhibit the apoptosis of human hepatic stellate cells, promote cell proliferation and migration; up regulation of miR-571 can promote the expression of Notch3 and Jagged1, and up-regulation of miR-571 also promoted the expression of related fibroblasts. MiR-571 can promote the activation of human stem cell stellate cells and the expression of fibroblast related factors through Notch3 signaling pathway.